Сатирична графіка Галичини другої пол.ХІХ ст. – поч.ХХ ст. очима сучасників - Іжевський, А. (Інститут народознавства НАН України, 2007)
This paper considers a state of satiric graphic evolution in Galicia basing on archived sources of the second half of 19-th – the first half of 20-th century. Articles and manuscripts of Lviv scientists and artists (I.Franko, V.Lozynsky, I.Trush, S.Moravsky, M.Holubets, E.Kosak not famous authors) were analyzed.